Loading stress distribution in posterior teeth restored by different core materials under fixed zirconia partial denture: a 3D-FEA study - Canipaner, Larissa Mendes [UNESP]; Pinto Metro, Amanda De Oliveira [UNESP]; Mendes Tribst, Joao Paulo; Souto Borges, Alexandre Luiz [UNESP]; Di Lauro, Alessandro Espedito; Lanzotti, Antonio; Garcia-Godoy, Franklin; Ausiello, Pietro (Mosher & Linder, Inc, 2021)
Purpose: To evaluate the effect of different substrate stiffness [sound dentin (SD), resin composite core (RC) or metal core (MC)] on the stress distribution of a zirconia posterior three-unit fixed partial denture (FPD). Methods: The abutment teeth (first molar and first premolar) were modeled, containing 1.5 mm of axial reduction, and converging axial walls. A static structural analysis was performed using a finite element method and the maximum principal stress criterion to analyze the fixed partial denture (FPD) and the cement layers of both abutment teeth. The materials were considered isotropic, linear, elastic, homogeneous and with bonded contacts. An axial load (300 N) was applied to the occlusal surface of the second premolar. Results: The region of the prosthetic connectors showed the highest tensile stress magnitude in the FPD structure depending on the substrate stiffness with different core materials. The highest stress peak was observed with the use of MC (116.4 MPa) compared to RC and SD. For the cement layer, RC showed the highest values in the molar abutment (14.7 MPa) and the highest values for the premolar abutment (14.4 MPa) compared to SD (14.1 and 13.4 MPa) and MC (13.8 and 13.3 MPa). Both metal core and resin composite core produced adequate stress concentration in the zirconia fixed partial denture during the load incidence. However, more flexible substrates, such as composite cores, can increase the tensile stress magnitude on the cement.